2015
DOI: 10.1093/annonc/mdu488
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomized study of whole-brain radiation therapy with or without concurrent temozolomide for brain metastases from breast cancer

Abstract: WBRT combined with TMZ did not significantly improve local control and survival in patients with BMs from breast cancer. CLINICALTRIALS.GOV: NCT00875355.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Randomized data have demonstrated that the addition of systemic therapy to WBRT increases both extracranial and CNS toxicity [28][29][30]. In a phase III trial, patients with NSCLC brain metastases were randomized to SRS + WBRT with or without temozolomide or erlotinib [31].…”
Section: Whole-brain Radiation Therapymentioning
confidence: 99%
“…Randomized data have demonstrated that the addition of systemic therapy to WBRT increases both extracranial and CNS toxicity [28][29][30]. In a phase III trial, patients with NSCLC brain metastases were randomized to SRS + WBRT with or without temozolomide or erlotinib [31].…”
Section: Whole-brain Radiation Therapymentioning
confidence: 99%
“…69 Increased GM-CSF content of orthotopic glioma bearing murine brain is immunosuppressive by increasing MDSC 31 in a parallel fashion as liver metastases generate local MDSC accretions by GM-CSF oversecretion. 76 Radiation of breast cancer brain metastases lowers lymphocyte count 77 but it has never been clear how. Concomitant radiation and temozolomide after GB resection induce decreased circulating lymphocytes.…”
Section: Elevated G(m)-csf Is Immunosuppressive In Gbmentioning
confidence: 99%
“…However, individually, only one out of 7 randomized controlled trials RCTs included in this meta-analysis showed a some survival improvement following the addition of temozolomide to radiotherapy, with median survival times of 7and 8.6 months in the RT arm and TMZ plus RT arm, respectively (15). In four randomized controlled trials that compare radiotherapy to concomitant TMZ and RT, the OS was lower in patients who were treated with combination TMZ and RT (11,(19)(20)(21) It is hard to compare the results of our study, that was performed on a homogenous group of patients ;with the previously mentioned studies which included more heterogeneous groups of patients and with different treatment regimens.…”
Section: Discussion:-mentioning
confidence: 89%